Electronic effects of nano-confinement in functional organic and inorganic materials for optoelectronics. (29th January 2021) - Ko, Jongkuk; Berger, Rüdiger; Lee, Hyemin; Yoon, Hyunsik; Cho, Jinhan; Char, Kookheon
Abstract : This review provides a comprehensive overview of the electronic effects of nano-confinement (from 1D to 3D geometries) on optoelectronic materials and their applications. Abstract : When various optically and/or electronically active materials, such as conjugated polymers, perovskites, metals, and metal oxides, are confined at the nanoscale, they can exhibit unique nano-confined behavior that significantly differs from the behavior observed at the macroscale. Although controlled nano-confinement of functional materials can allow modulation of their electronic properties without the aid of any synthetic methodologies or additional chemical treatments, limited assembly approaches for nano-confinement and insufficient analytical tools for electronic characterization remain critical challenges in the development of novel optoelectronic materials and the investigation of their modulated properties. This review describes how the nano-confined features of organic and inorganic materials are related to the control and improvement of their optoelectronic properties. In particular, we focus on various assembly approaches for effective nano-confinement as well as methods for nano-electronic characterization. Then, we briefly present challenges and perspectives on the direction of nano-confinement in terms of the preparation of optoelectronic materials with desired functionalities. Furthermore, we believe that this review can provide a basis for developing and designing next-generation optoelectronics through nano-confinement.